Aviation maintenance management - Kinnison, Harry A.; Siddiqui, Tariq (McGraw-Hill, 2013)
"The premier textbook for learning aircraft maintenance from a management perspective. Revised and up-dated to include recent technological, certification and maintenance updates"--Provided by publisher